Engineering Wood Products from Eucalyptus spp. - Lee Seng Hua; Lum Wei Chen; Petar Antov; Lubos Kristak; Paridah Md Tahir (Advances in Materials Science and Engineering)
Forest covers 4.06 billion hectares (ha) or 31% of the total land area worldwide, where 93% (3.75 billion ha) are natural regenerating forests and the remaining 7% (294 million ha) are planted forests. Eucalyptus spp., being one of the most important plantation species, has been planted in 95 countries around the world, and the area of plantation has exceeded 22.57 million ha. In the southern hemisphere, it is a significant industrial fast-growing tree species. These plantations serve as a valuable resource for the timber and fibre-based industries. Eucalyptus is the main fibre resource for the pulp and paper industries in developed countries. Timber extracted from the planted eucalyptus trees has long been used for solid wood and its fibres were used for manufacturing medium-density fibreboard. In comparison to most softwood species, Eucalyptus timber is reported to have a higher rigidity, making it ideal for manufacturing structural products. Therefore, this paper presents a review and analysis of the recent state of research on the utilisation of planted eucalyptus for engineered wood products (EWPs) manufacturing. This study investigated Eucalyptus-based EWPs such as particleboard, fibreboard, oriented strand board, laminated veneer lumber, plywood, glue laminated lumber, and cross-laminated lumber. The feasibility of using planted Eucalyptus in the production of EWPs, as well as the challenges encountered, was also discussed.